Physicochemical and Morphological Changes in Long-Grain Brown Rice Milling: A Study Using Image Visualization Technologies - Xiwu Jia; Rong Dong; Xuan Chen; Zhan Wang; Hongjian Zhang; Wangyang Shen (Foods)
This study evaluated the changes in physicochemical properties and appearance quality of long-grain rice during the grinding process using image technologies and aimed to provide reference for future research. The brown rice milling process was divided into three stages, and flatbed scanning, scanning electron microscopy (SEM), X-ray micro-computed tomography (micro-CT), low-field nuclear magic resonance (LF-NMR), and headspace–gas chromatography–ion mobility spectrometry (HS–GC–IMS) were employed to examine the physicochemical and volatile properties of the samples. Results revealed a continuous increase in the degree of milling, with a broken rice rate and a whiteness value increasing by 50.84% and 21.13%, respectively, compared with those during the initial stage; dietary fiber and vitamin B1 contents were reduced by 54.41% and 66.67%, respectively. The image results visualized showed that the cortex of brown rice was gradually peeled off with the increase in milling degree; the cortical thickness was gradually reduced, the endosperm was gradually exposed, and the surface was smoother and shinier. T2 populations exhibited a shift toward longer relaxation times, followed by a decrease in relaxation time during the milling process. Additionally, 31 target compounds impacting rice flavor, mainly ketones, alcohols, and esters, were identified, and the concentration of volatile substances in the B region decreased with the reduction in the bran layer; the concentration of volatile substances in the C region provided rice flavor, which increased with the milling process. This study showed changes in the physicochemical properties and appearance quality of long-grain brown rice during milling. Furthermore, the use of various image processing techniques offers significant insights for optimizing processing parameters and enhancing overall quality and taste.